The Impact of a Consumptive Lifestyle on the Household Economy in Indonesia - LuluAtul Al Insani; Naila Fauziah; Vika Azhari Almeida; Raden Ai Lutfi Hidayat (Escalate : Economics and Business Journal, 2026)
This study aims to analyze the impact of a consumptive lifestyle on household economics in Indonesia. The rapid development of technology, social media, and digital shopping platforms has influenced people’s consumption patterns, shifting spending from primary needs to secondary and tertiary desires. Using a qualitative descriptive method with literature study, observation, and semi-structured interviews of households in urban and semi-urban areas, this research reveals that consumptive behavior significantly weakens household financial stability. Excessive spending on non-essential goods and services reduces the ability to meet primary needs such as education, health, and savings, while also increasing the risk of household debt and financial stress. On a macroeconomic level, excessive consumption of luxury and imported goods contributes to trade deficits and decreases domestic economic resilience. Furthermore, low financial literacy exacerbates this problem, as many households struggle to differentiate between needs and wants, leading to poor financial management. The findings highlight that households with higher financial literacy and education levels are better at balancing consumption and maintaining economic resilience. Therefore, improving financial literacy, strengthening social awareness, and developing government policies that encourage productive and sustainable consumption are essential to mitigate the negative impact of a consumptive lifestyle.